2014
DOI: 10.2147/ijn.s59556
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced and selective delivery of enzyme therapy to 9L-glioma tumor via magnetic targeting of PEG-modified, ß-glucosidase- conjugated iron oxide nanoparticles

Abstract: The stability of enzyme-conjugated magnetic iron oxide nanoparticles in plasma is of great importance for in vivo delivery of the conjugated enzyme. In this study, β-glucosidase was conjugated on aminated magnetic iron oxide nanoparticles using the glutaraldehyde method (β-Glu-MNP), and further PEGylated via N-hydroxysuccinimide chemistry. The PEG-modified, β-glucosidase-immobilized magnetic iron oxide nanoparticles (PEG-β-Glu-MNPs) were characterized by hydrodynamic diameter distribution, zeta potential, Four… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 28 publications
0
15
0
Order By: Relevance
“…The characteristic peak at 1689.46 cm −1 revealed the presence of an amide-I region of Tm-β-Glu which confirmed the successful immobilization of Tm-β-Glu onto Ch-MNPs. The broadband at around 3320 cm −1 after immobilization of Tm-β-Glu-Tt-ChBD could be due to association intermolecular bonds from N-H stretching vibration with O-H stretching vibration in the β-Glu molecules 28 , which confirmed successful immobilization of Tm-β-Glu-Tt-ChBD on Ch-MNPs. www.nature.com/scientificreports www.nature.com/scientificreports/ Also, through the analysis of user access strategies in the correlation between Fe 3 O 4 MNPs synthesis with Tm-β-Glu-Tt-ChBD and specificity binding through target molecules using AutoDock software to design and correlation analysis.…”
Section: Results and Discussion Production Of Recombinant Tm-β-glu Fumentioning
confidence: 70%
“…The characteristic peak at 1689.46 cm −1 revealed the presence of an amide-I region of Tm-β-Glu which confirmed the successful immobilization of Tm-β-Glu onto Ch-MNPs. The broadband at around 3320 cm −1 after immobilization of Tm-β-Glu-Tt-ChBD could be due to association intermolecular bonds from N-H stretching vibration with O-H stretching vibration in the β-Glu molecules 28 , which confirmed successful immobilization of Tm-β-Glu-Tt-ChBD on Ch-MNPs. www.nature.com/scientificreports www.nature.com/scientificreports/ Also, through the analysis of user access strategies in the correlation between Fe 3 O 4 MNPs synthesis with Tm-β-Glu-Tt-ChBD and specificity binding through target molecules using AutoDock software to design and correlation analysis.…”
Section: Results and Discussion Production Of Recombinant Tm-β-glu Fumentioning
confidence: 70%
“…Recently, several reports have indicated that magnetic nanoparticles combined with an external magnetic field could be used for the transportation of drugs across the BBB30,31 . Seong Deok Kong et al first noticed that magnetic nanoparticles could cross the normal BBB when subjected to an external magnetic field.…”
mentioning
confidence: 99%
“…This was diluted in cell culture media to 100 μg/mL, either in DMEM or RPMI, both supplemented with 10% fetal bovine serum (FBS). DMEM and RPMI are common cell culture media formulated from salts, vitamins and amino acids; the two different media contain the same components but differ in the relative concentrations notably of Ca 2+ and PO 4 3− ions 8 . Henceforth, DMEM/RPMI is referred to as cell culture media (CCM) and when supplemented with 10% FBS is referred to as complete cell culture media (CCCM).…”
Section: Methodsmentioning
confidence: 99%
“…There is increasing evidence and understanding of the potential therapeutic benefits of using nanotechnology within medicine 1,2 . A wide range of nanoparticles have been studied and shown promise in applications such as drug delivery, medical imaging and cancer therapy [3][4][5][6] . Typically such nanomedical studies require nanoparticles to be dispersed in biological fluids.…”
mentioning
confidence: 99%